2014
DOI: 10.1161/circgenetics.113.000294
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs and the Occurrence of Acute Myocardial Infarction in Chinese Populations

Abstract: A cute myocardial infarction (AMI) is a leading cause of morbidity and mortality worldwide. 1 Multiple conventional risk factors and serum atherosclerotic biomarkers have been established for coronary heart disease (CHD). 2 However, advances in genomics and proteomics, especially gene-expression profiling using microarray and quantitative real-time polymerase chain reaction (qPCR), have promoted the generation of many novel molecular biomarkers for AMI with potential clinical values. 3,4 Recently, microRNAs (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…According to previous researches, miRNA was involved in the physiological process of apoptosis, electrical conduction change, cardiomyocytes regeneration and cardiac remodeling during the myocardial ischemia and anoxia [14][15][16][17]. Besides, several researches have explained the mechanism of many miRNAs in the acute myocardial ischemia, which provide the reference for the treatment of heart diseases through the molecular drugs.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous researches, miRNA was involved in the physiological process of apoptosis, electrical conduction change, cardiomyocytes regeneration and cardiac remodeling during the myocardial ischemia and anoxia [14][15][16][17]. Besides, several researches have explained the mechanism of many miRNAs in the acute myocardial ischemia, which provide the reference for the treatment of heart diseases through the molecular drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the RNA pellet was purged with 1 mL ethanol (75% v/v) to remove residual salt. For normalization, each sample was supplemented with 25 pM Caenorhabditi selegans miR-39 (cel-miR-39) after the addition of TRIzol, as previously reported [35].…”
Section: Plasma Microrna Isolation and Validationmentioning
confidence: 99%
“…39 When we prepared for this study, we also demonstrated in another study that plasma level of miR-320b was significantly lower in acute myocardial infarction patients compared with control subjects. 40 MiR-27a-3p was involved in endothelial cell pathophysiology, 41 and miR-142-5p expression was decreased in the peripheral blood mononuclear cells of chronic heart failure patients. 42 Moreover, the predicted target genes of miR-142-5p overlapped much with the known chronic heart failure-modulated genes.…”
Section: Discussionmentioning
confidence: 96%